2016
DOI: 10.4236/jmmce.2016.43019
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Treatment Effects of Blue, Yellow and Green Colors with Heating Methods on Agates of Cheshme Shoor Area, Qom, Iran

Abstract: The Cheshme Shoor area is located in northeast of Qom which is a part of central Iran geo-structural zone. The rocks of the area are mainly volcanic rocks that include Eocene acidic tuffs and ignimbrites. Different types of agate, jasper and amethyst formed as secondary cavity filling deposits in variety of colors and shapes in the area. In this paper, chemical treatments by different chemicals with heating methods in 15 different procedures have been conducted on one agate sample of the study area which has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Treatment methods are used in pale-colored agates that are not considered to be visually sufficient. Therefore, color treatments are made in agates by methods such as dyeing and heat treatment (Hajalilou and Vosug 2008;yazdi, et. al.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment methods are used in pale-colored agates that are not considered to be visually sufficient. Therefore, color treatments are made in agates by methods such as dyeing and heat treatment (Hajalilou and Vosug 2008;yazdi, et. al.…”
Section: Introductionmentioning
confidence: 99%
“…Heating stages are usually conducted in wood or gas-fired ovens. A specific discussion on local agate dyeing techniques is presented here, but a comprehensive review of methods to enhance the appearance and color of gemstones can be found in Nassau (1984;1994) while Tubino and Sampaio (2000) and Yazdi et al (2016) present specific information about chemical treatments of agates.…”
Section: Introductionmentioning
confidence: 99%